MicroRNA-101-3p regulates gastric cancer cell proliferation, invasion and apoptosis by targeting PIM 1 expression - Wu, Fubing; Huang, Wen; Yang, Lili; Xu, Fanggui (Cellular and Molecular Biology, 2019)
To investigate the effect of microRNA-101-3p (miRNA-101-3p) on proliferation, invasion and apoptosis of gastric cancer (GC) cells, and to explore its influence mechanism. Human GC cell line (AGS) and normal human gastric epithelial cell line (GES-1) were used in this study. The cells were transfected with proto-oncogene serine/threonine-protein kinase (PIM 1) overexpression plasmid, miRNA-101-3p mimics, or miRNA-101-3p non-homologous sequence using lipofectamine 2000. Real-time quantitative polymerase chain reaction (qRT-PCR) and Western blotting were used to determine the expressions of miRNA-101-3p and PIM 1 in GC cells. Cell counting kit-8 (CCK-8) and Transwell assays were used to assess the effect of miRNA-101-3p on proliferation and invasion of GC cells. The regulatory effect of miRNA-101-3p on PIM 1 was assessed using bioinformatics analysis and luciferase reporter gene assay. The expression of miRNA-101-3p was significantly down-regulated in GC cells, relative to normal human gastric epithelial cells (p < 0.05). However, the expression of PIM 1 mRNA was significantly upregulated in GC cells, when compared with normal gastric epithelial cells (p < 0.05). The expression level of miRNA-101-3p was significantly higher in miRNA-101-3p mimic group than in miRNA-101-3p control and normal control groups (p < 0.05). Cell proliferation in miRNA-101-3p mimic group was significantly and time-dependently reduced, when compared with miRNA-101-3p control and normal control groups (p < 0.05). Transfection with miRNA-101-3p mimics significantly increased the invasiveness of AGS cells, and significantly promoted their apoptosis (p < 0.05). Results of qRT-PCR and Western blotting showed that increased miRNA-101-3p expression significantly reduced the expression of PIM 1, while decreased miRNA-101-3p expression promoted the expression of PIM 1 (p < 0.05). Results of bioinformatics showed that miRNA-101-3p had specific binding sequence in the 3’UTR region of PIM 1. Cloning of miRNA-101-3p sequence into the luciferase reporter plasmid led to significant inhibition of the expression of PIM 1 (p < 0.05), but had no inhibitory effect on mutated PIM 1 3’UTR (p > 0.05). Overexpression of PIM 1 significantly reversed the inhibition of proliferation and invasion, and promotion of apoptosis by miRNA-101-3p (p < 0.05). These results indicate that miRNA-101-3p inhibits the proliferation and invasion of GC cells, and promotes their apoptosis by regulation of the expression of PIM-1.